ON THE LEONTIEF DYNAMIC INVERSE. - Kendrick, David (Quarterly Journal of Economics)
In this article the author comments on the theory developed by the economist Wassily Leontief, on the dynamic inverse approach for solving dynamic multisectoral models. According to the author Leontief's method avoids the well-known difficulty of a singular capital matrix but ignores problems of consistency with initial conditions. While consistency may be obtained through iterative selection of terminal conditions, this procedure would be computationally difficult for models with many sectors. Here the author suggests a method which obviates the necessity of iteration by integrating forward in time from the initial conditions and overcomes the singularity problem through the use of a partitioning procedure. This forward integration procedure has the intuitive advantage that it works from given initial conditions and that an interactive procedure is not required. The author remarks that while the computational gain would be of small importance in models with a few sectors, it would be of major importance in dynamic models.